Effects of adaptive harvesting on fishing down processes and resilience changes in predator-prey and tritrophic systems - Tromeur, Eric; Loeuille, Nicolas (Peer Community Journal, 2023)

(untitled)
Many world fisheries display a declining mean trophic level of catches. This “fishing down the food web” is often attributed to reduced densities of high-trophic-level species. We show here that the fishing down pattern can actually emerge from the adaptive harvesting of two- and three-species food webs, where changes in fishing patterns are driven by the relative profitabilities of the harvested species. Shifting fishing patterns from a focus on higher trophic levels to a focus on lower trophic levels can yield abrupt changes in the system, strongly impacting species densities. In predator-prey systems, such regime shifts occur when the predator species is highly valuable relative to the prey, and when the top-down control on the prey is strong. Moreover, we find that when the two species are jointly harvested, high adaptation speeds can reduce the resilience of fisheries. Our results therefore suggest that flexibility in harvesting strategies will not necessarily benefit fisheries but may actually harm their sustainability.